Peran Patroli Satuan Sabhara Kendaraan Bermotor Roda Dua Dalam Mencegah Tindak Pidana Pencurian Dengan Pemberatan Di Wilayah Hukum Polres Majalengka - Jody Wisnu Sadewo (Indonesian Journal of Police Studies, 2020)
The highest of criminal acts in the jurisdiction of Majalengka Regional Police is Curat. This relates to the task that is owned by the Sat Sabhara Patrol Unit which is the spearhead for taking preventative actions against the Curat crime. In this thesis the author tries to understand how the description of the implementation of patrols using motorized vehicles R2 to prevent felony. Starting from what caused the Curat crime to occur in Majalengka district as well as the factors that influence the Curat preventive action by patrol using R2 motor vehicles. The purpose of this research is to know the description of the occurrence of Curat crime, the description of the implementation of Patrol using R2 motor vehicles, and to know the factors that influence the implementation of Patrol activities using R2 motorized vehicles in preventing Curat. This study uses the concept of Patrol, management theory and routine activity theory with a qualitative approach which is to dig information to find facts. The findings in this study are the first, Curat crimes that occur due to the economic impetus of the perpetrators and the absence of the police which led to meeting the intentions and opportunities of the perpetrators of Curat. Secondly, the implementation of Patrol using R2 motor vehicles carried out by the Sat Sabhara Patrol Unit was affected by internal and external factors. Advice given by the first author, in conducting patrols, it must reach the entire area of ​​Majalengka to eliminate the intentions of the perpetrators. Second, revise the SOP for conducting patrols using two-wheeled motor vehicles based on the latest regulations. Second, for the Sat Sabhara Patrol Unit to increase the number of Sat Sabhara Patrol Unit personnel.